2011
DOI: 10.1016/j.biortech.2010.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding regimens on polyhydroxybutyrate production from food wastes by Cupriavidus necator

Abstract: List of abbreviations: PHA, polyhydroxyalkanoate; PHB, polyhydroxybutyrate; DO, dissolved oxygen; DCW, dry cell weight; COD, chemical oxygen demand; VFA, volatile fatty acid; D-COD, dissolved chemical oxygen demand; GC, gas chromatography; PHB-PHV, poly(3-hydroxybutyrate-co-3-hydroxyvalerate) 2 ABSTRACT We investigated the effects of different feeding regimens (1-pulse, stepwise, and continuous) of fermented food-waste liquid on polyhydroxybutyrate (PHB) production.The fermentation liquid was filtered with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 11 publications
3
30
0
1
Order By: Relevance
“…62 Another fed-batch strategy involving substrate feeding at a constant feed rate for P(3HB) production has been described. 31,64 A novel exponential feeding strategy based on alkali-addition monitoring was developed to maintain waste glycerol (substrate) at a constant level inside the bioreactor. 65 It resulted in a significantly high P(3HB) concentration of 65.6 g L -1 , yield of 62.7 % dcw, and productivity of 1.3 g L -1 h -1…”
Section: Fed-batch Fermentationmentioning
confidence: 99%
“…62 Another fed-batch strategy involving substrate feeding at a constant feed rate for P(3HB) production has been described. 31,64 A novel exponential feeding strategy based on alkali-addition monitoring was developed to maintain waste glycerol (substrate) at a constant level inside the bioreactor. 65 It resulted in a significantly high P(3HB) concentration of 65.6 g L -1 , yield of 62.7 % dcw, and productivity of 1.3 g L -1 h -1…”
Section: Fed-batch Fermentationmentioning
confidence: 99%
“…necator, are recognized as amazing pollutant-degrading bacteria (4, 5). Studies also show that they are efficient platforms for the production of polyhydroxyalkanoates (PHAs), which are promising substitutes for conventional petrochemical plastics due to their biodegradable and biocompatible merits, as they use waste material as a substrate (6, 7). Here, the genome sequence of Cupriavidus sp.…”
Section: Genome Announcementmentioning
confidence: 99%
“…While, pH-stat feeding has been employed by most of the researchers to feed short chain fatty acids (Kobayashi et al, 2000;Sugimoto et al, 1999;, for lactic acid and a mixture of lactic and acetic acids, feeding at different time intervals that is intermittent feeding strategy has been found to be more suitable (Tsuge et al, 2001;Linko et al, 1993;Tanaka et al, 1993). Very recently, Hafuka et al (2011) reported high PHB content (~87%) by continuous feeding of filtered fermented food wastes in C. necator. However, the biomass and PHB production rate was quite low as compared to others.…”
Section: Fed-batch Cultivation In Bioreactor For Phb Productionmentioning
confidence: 99%
“…Significant research has been focused on using organic acids from fermented food wastes as raw materials for PHA production (Hafuka et , 2011;Du and Yu, 2002;Du et al, 2004). However, food waste in developing countries is usually denser than in developed areas, and its composition is an indicator of the socio-economic situation of the population (Holmes, 1984).…”
Section: Introductionmentioning
confidence: 99%